Identify all of the terms containing y. In this equation, the only y term is on the left side. Identify all the terms on that (left) side that do not contain y. Subtract those terms from both sides of the equation.

2x + y = 11

2x + y - 2x = 11 - 2x (subtract the "not y" term)

y = 11 - 2x (simplify)

_____

If the resulting equation has a y coefficient that is not 1, divide the equation by it.

2x + y = 11

2x + y - 2x = 11 - 2x (subtract the "not y" term)

y = 11 - 2x (simplify)

_____

If the resulting equation has a y coefficient that is not 1, divide the equation by it.